2006
DOI: 10.1177/0731684405056432
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Waste Silk Fabric as Reinforcement for Acrylonitrile Butadiene Styrene Toughened Epoxy Matrix

Abstract: The blend matrix epoxy-acrylonitrile butadiene styrene (ABS) is prepared with varying weight percentage (2, 4, 6, 8, and 10) of ABS content in epoxy and the tensile, flexural, and impact properties of this blend matrix is determined. The blend matrix, which contains 4% ABS content in epoxy shows maximum strength and this is used as the matrix to prepare composites. Composites are prepared with varying weight fraction of silk fabric as the reinforcement and pure epoxy and ABS-epoxy as matrix. The developed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Therefore, low thermal conductivity of the covalent bond structure will shorten its serving time. This defect can be overcome by mixing it with inorganic fillers, such as ZnO, CaCO 3 , hollow glass beads, Al 2 O 3 , wood dust, waste silk fabric, textile fibre, and fly ash …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, low thermal conductivity of the covalent bond structure will shorten its serving time. This defect can be overcome by mixing it with inorganic fillers, such as ZnO, CaCO 3 , hollow glass beads, Al 2 O 3 , wood dust, waste silk fabric, textile fibre, and fly ash …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Therefore, low thermal conductivity of the covalent bond structure will shorten its serving time. This defect can be overcome by mixing it with inorganic fillers, such as ZnO, 22 CaCO 3 , 23-25 hollow glass beads, 26 Al 2 O 3 , 19 wood dust, 27 waste silk fabric, 28 textile fibre, 21 and fly ash. 29 Among the multiple factors that influence the useful properties of polymer/inorganic composites, the filler dispersion and interfacial interactions are the crucial ones between the matrix and the inorganic filler.…”
Section: Introductionmentioning
confidence: 99%
“…FRPCs find applications in construction industries, 72 decking, window and door frames, 7376 sports equipment such as bicycle frames, baseball bats, exercise equipment, and so on. 77 They are also suited for many automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…The waste silk fabrics from a local silk manufacturer were collected for the purpose of reinforcement. In an earlier study [9], it was proven that the blend containing 4 wt% of acrylonitrile-butadiene-styrene (ABS) in epoxy (which is used as a matrix for the preparation of the composites in the current study) was shown to have better properties when compared to the other combinations of the blend prepared with 2, 6, 8, and 10 wt% of ABS in epoxy.…”
Section: Introductionmentioning
confidence: 82%